The Toxic Effect of Ametryn on Behaviour and Histopathological Changes of Freshwater Eel (Monopterus Albus) [Pengaruh Toksik Ametryn terhadap Perilaku dan Perubahan Histopatologis Belut AirTawar (Monopterus Albus)] - Marina Hasan; Nor Azri Shah Norhan; Wahidah Wahab; Anur Abdalah Nagi Melad; Kismiyati Kismiyati; Mohd Fazrul Hisam Abd Aziz; Norainy Mohd Husin; Mohd Ihwan Zakariah (Jurnal Ilmiah Perikanan dan Kelautan, 2019)
AbstractA study on the toxicity of herbicides was investigated with emphasis on behaviour and histopathological effects. Ametryn commonly used to control weeds in the paddy field. The effect of ametryn on fish especially Monopterus albus was unknown. This study aims to determine the acute toxicity of ametryn and its effects on the behaviour of the eels. The adult M. albus were exposed to 0, 0.75, 1.5 and 3.0mg/L of ametryn for 96 hours under laboratory conditions. The eels showed symptoms of abnormal behaviour responses during the exposure which are agitated behaviour, respiratory distress, and abnormal nervous behaviour. Mortality was increased by increasing the concentration of ametryn. This present study showed the effect of ametryn on kidney tissue changes. Hemorrhage and distribution of hemosiderin, hydropic degeneration, granular degeneration, tubular necrosis, narrowing tubular lumen and necrosis were major histopathological effects that occurred during the exposure to ametryn. In conclusion, ametryn is very sensitive to Monopterus albus. In lower concentration, they showed changes in behaviour and effect their organs. AbstrakStudi tentang toksisitas herbisida yang diamati dengan penekanan pada perilaku dan dampak histopatologis. Ametryn biasanya digunakan untuk mengawal rumpai di sawah padi. Kesan ametryn pada ikan terutama belut tidak diketahui. Penelitian ini bertujuan untuk menentukan toksisitas akut ametryn dan dampaknya terhadap perilaku belut. M. albus dewasa terpapar pada 0, 0.75, 1,5 dan 3,0mg / L ametryn selama 96 jam pada kondisi laboratorium. Belut menunjukkan gejala respons perilaku abnormal selama paparan yaitu gelisah, gangguan pernapasan, dan perilaku saraf abnormal. Kematian meningkat seiring meningkatnya konsentrasi ametryn. Penelitian ini menunjukkan dampak ametryn pada perubahan jaringan ginjal. Perdarahan dan distribusi hemosiderin, degenerasi hidropik, degenerasi granular, nekrosis tubular, penyempitan lumen tubular dan nekrosis adalah dampak histopatologis utama yang terjadi selama paparan ametryn. Kesimpulannya, ametryn sangat sensitif terhadap Monopterus albus. Dalam konsentrasi rendah, belut menunjukkan perubahan perilaku dan kesan pada organ.